Polygala retiefiana (Polygalaceae), a new species described from South Africa - Paiva, Jorge; Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2013)
A new species of Polygala (Polygalaceae), P. retiefiana, is described from the KwaZulu-Natal and Free State provinces of South Africa. It is endemic to the country.